PARTICIONAMENTO DE PINOS DE I/O E SEU IMPACTO NO TAMANHO DAS INTERCONEXÕES E NÚMERO DE VIAS EM CIRCUITOS VLSI 3D - Sawicki, Sandro; Hentschke, Renato; Johann, Marcelo; Reis, Ricardo (Salão do Conhecimento, 2013)
Resumo